Does Risk Perception and Knowledge of Covid-19 Correspond with Vaccination Decision? - Manalu, Rouli; Pradekso, Tandiyo; Setyabudi, Djoko; Budiarsa, Yohanes Thianika (Ikatan Sarjana Komunikasi Indonesia, 2023)
This research examines the correlation between perception of risk of Covid-19 and knowledge of Covid-19 to reach vaccination decisions. A number of researches have shown that among many factors that are associated with people’s decision to get vaccinated are the perception of how vulnerable are they to be infected by the virus and the perception of how severe is the impact of the virus on them as well as how knowledgeable are they about the disease being prevented. This research aims to investigate the same finding in the context of a group of respondents in Indonesia. With the online survey that collected data of more than three hundred research participants, the result of the data analysis in this research, however, does not corroborate the finding in the previous research. Part of the possible explanation is the approach to drive the vaccination through the implementation of the vaccine mandate. The policy of vaccine mandate in Indonesia was implemented since the vaccine was first available in the country. The proof of vaccination was used as a requirement to have access to public transportations and other public services. This vaccine mandate continued progressively to the second and even third or booster vaccination. This policy of mandatory vaccination became an approach to increase vaccine uptake, which was rather different from other vaccinations that allow some room for voluntary choices.